STUDENTS' PERCEPTIONS OF BLENDED LEARNING IN ENGLISH LANGUAGE EDUCATION: A MIXED-METHOD STUDY OF EXPERIENCES AND CHALLENGES - adminjurnal adminjurnal; Treesly Yumiardi Normin Adoe; Habibi Musa (SENSEI RESEARCH CENTER, 2025)
After the pandemic, blended learning is still used in many universities because it is more flexible. However, not all students feel comfortable with this model. This study discusses students' perceptions of blended learning in English language education. The study used a mixed-method design. The data were collected through a questionnaire and interviews with the students. The data were analyzed descriptively and thematically. The result shows that the perception of the students towards blended learning is generally positive, especially about the flexibility, but there are also some problems such as internet connection and the students are sometimes confused because the online and offline activities are not connected. Therefore the lecturers should design blended learning better.